Local Borcherds products for unitary groups - Hofmann, Eric (Nagoya mathematical journal, 2017)
For the modular variety attached to an arithmetic subgroup of an indefinite unitary group of signature (1, n+1), with n >= 1, we study Heegner divisors in the local Picard group over a boundary component of a compactification. For this purpose, we introduce local Borcherds products.